Nitrogen modulates cotton root morphology by affecting abscisic acid (ABA) and salicylic acid (SA) content. Issue 12 (15th October 2021) - Chen, Jing; Liu, Shaodong; Zhang, Siping; Ge, Changwei; Shen, Qian; Ma, Huijuan; Zhang, Xiaomeng; Dong, Helin; Zhao, Xinhua; Pang, Chaoyou
ABSTRACT: A hydroponic experiment was conducted to explore the effects of nitrogen on cotton root morphology and related hormone contents and to analyse the correlation between the indexes. The effects of different nitrogen concentrations (N0, N1, N2, and N3 with 0, 2, 4, and 8 mmol l −1, respectively) on main and lateral roots were evaluated. A moderate nitrogen concentration (N2, 4 mmol l −1 ) promotes root growth. Lateral roots responded quickly to changes in nitrogen concentrations. Compared with N0 treatment, N2 treatment resulted in significantly greater main root volume after 12 days as well as increased lateral root length, root projected area, root surface area, and root volume after 8 days. Nitrogen significantly decreased abscisic acid (ABA), salicylic acid (SA), and isopentenyladenine (iP) content, which were the lowest in N2 treatment (33.92% lower than N0). The ABA and SA content were negatively correlated with root morphology. This shows that a moderate nitrogen concentration (4 mmol l −1 ) significantly decreased ABA and SA content in the main and lateral roots and promoted root growth in cotton plants. These results will contribute to root growth theory regarding efficient nitrogen utilization by cotton plants and will provide a theoretical basis to ensure nitrogen resources are utilized efficiently.